2023
DOI: 10.1002/advs.202302325
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Detoxification of Trans, Trans‐2,4‐Decadienal, an Oxidation Product from Omega‐6 Fatty Acids, Alters Insulin Signaling, Gluconeogenesis and Promotes Microvascular Disease

Xin Qian,
Stephan Klatt,
Katrin Bennewitz
et al.

Abstract: Omega‐6 fatty acids are the primary polyunsaturated fatty acids in most Western diets, while their role in diabetes remains controversial. Exposure of omega‐6 fatty acids to an oxidative environment results in the generation of a highly reactive carbonyl species known as trans, trans‐2,4‐decadienal (tt‐DDE). The timely and efficient detoxification of this metabolite, which has actions comparable to other reactive carbonyl species, such as 4‐hydroxynonenal, acrolein, acetaldehyde, and methylglyoxal, is essentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 90 publications
(128 reference statements)
0
1
0
Order By: Relevance
“…Approximately one-third of diabetes patients develop DR ( 21 ). Recent studies revealed that the pathological processes of DR were associated with long-term metabolic disturbances ( 9 , 27 , 28 ). With the advancement of metabolomics, metabolites and metabolic pathways associated with DR are continuously being discovered ( 10 , 27 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Approximately one-third of diabetes patients develop DR ( 21 ). Recent studies revealed that the pathological processes of DR were associated with long-term metabolic disturbances ( 9 , 27 , 28 ). With the advancement of metabolomics, metabolites and metabolic pathways associated with DR are continuously being discovered ( 10 , 27 , 29 ).…”
Section: Discussionmentioning
confidence: 99%